2016
DOI: 10.7554/elife.20391
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegenerative disease mutations in TREM2 reveal a functional surface and distinct loss-of-function mechanisms

Abstract: Genetic variations in the myeloid immune receptor TREM2 are linked to several neurodegenerative diseases. To determine how TREM2 variants contribute to these diseases, we performed structural and functional studies of wild-type and variant proteins. Our 3.1 Å TREM2 crystal structure revealed that mutations found in Nasu-Hakola disease are buried whereas Alzheimer’s disease risk variants are found on the surface, suggesting that these mutations have distinct effects on TREM2 function. Biophysical and cellular m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
228
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 170 publications
(243 citation statements)
references
References 68 publications
(107 reference statements)
15
228
0
Order By: Relevance
“…A crystal structure of TREM2 also found a potential phospholipid binding site that is largely consistent with the model structure shown [120]. In addition, the authors concluded that residues mutated in NHD were buried and could impact [ 5 6 9 _ T D $ D I F F ] protein folding, while the AD-associated residues were found on the surface and could affect ligand binding [120]. longer encodes a transmembrane (TM) domain, producing a TREM2 protein that is presumed to be soluble and secreted.…”
Section: Extracellular Ligands Of Trem2supporting
confidence: 77%
See 1 more Smart Citation
“…A crystal structure of TREM2 also found a potential phospholipid binding site that is largely consistent with the model structure shown [120]. In addition, the authors concluded that residues mutated in NHD were buried and could impact [ 5 6 9 _ T D $ D I F F ] protein folding, while the AD-associated residues were found on the surface and could affect ligand binding [120]. longer encodes a transmembrane (TM) domain, producing a TREM2 protein that is presumed to be soluble and secreted.…”
Section: Extracellular Ligands Of Trem2supporting
confidence: 77%
“…The putative structure of the TREM2 Ig-like domain showed that there is a prominent patch of hydrophobic amino acids with adjacent positively charged residues, a potential binding pocket for phospholipids, that by contrast was not found on the surface of TREM1 -which does not interact with phospholipids [117] (Figure 5). A crystal structure of TREM2 also found a potential phospholipid binding site that is largely consistent with the model structure shown [120]. In addition, the authors concluded that residues mutated in NHD were buried and could impact [ 5 6 9 _ T D $ D I F F ] protein folding, while the AD-associated residues were found on the surface and could affect ligand binding [120].…”
Section: Extracellular Ligands Of Trem2supporting
confidence: 63%
“…The association of distinct variants with different diseases is born out on the protein level. Structural, biophysical, and cellular studies have shown the NHD coding mutants are misfolded with immature glycosylation patterns while the AD variants are properly folded and have mature glycosylation patterns but likely impact ligand binding [25, 26] (Fig 1C and Table 2). Slightly altered glycosylation patterns have been observed for the R47H variant [27, 28], but it is unclear if these have functional ramifications.…”
Section: Trem2 In Diseasementioning
confidence: 99%
“…Pathway analysis identified the TREM2 co-receptor DAP12 as a key regulator of expression changes in LOAD [35]. Although there have been reports of TREM2 detection on non-myeloid/microglial cells in the CNS [4, 36], these cases have largely used immunostaining methods to identify neuronal expression of TREM2, which may identify sTREM2 produced by microglia that is released and bound to neurons which express a TREM2 ligand [26, 3739]. RNA expression analyses have confirmed Trem2 is expressed selectively on microglia in the brain [40, 41], and parabiosis experiments show these microglia are most likely resident microglia and not infiltrating monocytes [42], although this is still controversial [43].…”
Section: Trem2 In Diseasementioning
confidence: 99%
“…Recent accumulating evidence reveals an association between a diverse array of TREM2 variants and risk for AD and other neurodegenerative diseases [10][11][12]. These variants include mutations affecting TREM2 structure/function such as the generation of a truncated protein (W44X or W78X variants) [21], inability to associate with its intracellular adaptor, DAP12/TYROBP (K186N variant) [21], reduction in ligand binding ability (R47H variant) [22][23][24], alteration of subcellular localization (reduction on cell surface and increase in endoplasmic reticulum in T66M or Y38C variants) [18,25] and accelerated proteolytic loss from the cell surface (H157Y variant) [19,20]. Therefore, TREM2-related microglial dysfunction can potentially lead to the impairment of brain homeostasis including amyloid-β clearance, possibly leading to neuronal injury and cognitive dysfunction.…”
Section: Emerging Implications Of Trem2 and Strem2 In Neurodegeneratimentioning
confidence: 99%